In vitro effects of a small-molecule antagonist of the Tcf/ß-catenin complex on endometrial and endometriotic cells of patients with endometriosis. - Sachiko Matsuzaki (Public Library of Science (PLoS), 2013)
Background Our previous studies suggested that aberrant activation of Wnt/ß-catenin signaling might be involved in the pathophysiology of endometriosis. We hypothesized that inhibition of Wnt/ß-catenin signaling might result in inhibition of cell proliferation, migration, and/or invasion of endometrial and endometriotic epithelial and stromal cells of patients with endometriosis. Objectives The aim of the present study was to evaluate the effects of a small-molecule antagonist of the Tcf/ß-catenin complex (PKF 115-584) on cell proliferation, migration, and invasion of endometrial and endometriotic epithelial and stromal cells. Methods One hundred twenty-six patients (78 with and 48 without endometriosis) with normal menstrual cycles were recruited. In vitro effects of PKF 115-584 on cell proliferation, migration, and invasion and on the Tcf/ß-catenin target genes were evaluated in endometrial epithelial and stromal cells of patients with and without endometriosis, and in endometrial and endometriotic epithelial and stromal cells of the same patients. Results The inhibitory effects of PKF 115-584 on cell migration and invasion in endometrial epithelial and stromal cells of patients with endometriosis prepared from the menstrual phase were significantly higher than those of patients without endometriosis. Levels of total and active forms of MMP-9 were significantly higher in epithelial and stromal cells prepared from menstrual endometrium in patients with endometriosis compared to patients without endometriosis. Treatment with PKF 115-584 inhibited MMP-9 activity to undetectable levels in both menstrual endometrial epithelial and stromal cells of patients with endometriosis. The number of invasive cells was significantly higher in epithelial and stromal cells of endometriotic tissue compared with matched eutopic endometrium of the same patients. Treatment with PKF 115-584 decreased the number of invasive endometriotic epithelial cells by 73% and stromal cells by 75%. Conclusions The present findings demonstrated that cellular mechanisms known to be involved in endometriotic lesion development are inhibited by targeting the Wnt/β-catenin pathway.